Optimised biopolymer-based capsules for enhancing the mechanical and self-healing properties of asphalt mixtures - Jose Norambuena-Contreras (Materials and Structures, 2024)
The growing need to enhance our road infrastructure has driven the development of several innovative techniques in recent years. Among these advancements, encapsulated rejuvenator solutions for extrinsic self-healing asphalt have emerged as a significant topic of interest. This paper evaluates the effect of optimised capsules containing vegetal oil as a biorejuvenator on the physical, mechanical, and self-healing properties of dense asphalt mixtures. In this study, previously optimised polynuclear alginate-based capsules were synthesised using vibrating jet technology with 5% wt. calcium chloride and a biopolymer-to oil mass ratio 1:7. Optimised capsules were incorporated into the asphalt mixture at concentrations of 0.125% wt., 0.25% wt., and 0.5% wt. Their spatial distribution within the asphalt mixtures was evaluated using an alternative method to CT scans, which utilised machine learning-based image analysis of the core asphalt samples. The main findings of this research are as follows: (1) a uniform distribution of capsules was achieved throughout the asphalt mixture, although clustering was observed at higher concentrations. (2) The capsules successfully survived the asphalt manufacturing process, and mechanical tests highlighted the adhesive properties of the alginate encapsulation material. (3) Asphalt samples with 0.125% wt. capsules exhibited mechanical performance comparable to samples without capsules; however, this content did not significantly enhance their self-healing properties. In contrast, self-healing capabilities were significantly enhanced with a capsule content greater than or equal to 0.25% wt.; however, this enhancement slightly affected some physical–mechanical properties of the dense asphalt mixture.